Avaliação dos parâmetros que influenciam nas alterações dimensionais e nas tensões residuais do polipropileno moldado por injeção - Scopel, Tiago (My University, 2018)
The final quality of the injection molded polymer products can be compromised due to the occurrence of residual stresses from the molding process, which can generate shrinkage and warpage, altering the final product dimensions. The determination of the residual stresses can be carried out by the hole-drilling method, which is not widely used for polymeric materials since it is standardized for metallic materials. Therefore, in order to evaluate the main parameters that influence in the dimensional change and in the residual stresses of the injection molded polypropylene, this report used computer simulation, thermal analysis, warpage and shrinkage measurements, tensile and impact strength tests and evaluation of the residual stresses by hole-drilling method. After molding, the specimens were submitted to three post-molding conditions (physical restraint + water, physical restraint + heating chamber, neutral). In the experimental tests, the molded specimens with lower packing pressure, as well as the ribbed molded showed greater warpage, which corroborated the computer simulations and the literature. In the post-molding conditions, it was observed that the smooth specimens submitted to the physical restraint + heating chamber showed lower warpage in relation to those that were not submitted to this condition. Regarding the shrinkage, for both geometries specimens, there were not significant variations of the averages. The thermal analysis presented lower crystallinity in the specimens with neutral post-molding condition in relation to the physical restraint + heating chamber condition. The residual stresses analysis concluded that ribbed specimens showed greater residual stresses than smooth specimens, which corroborates the literature which indicates higher concentration of residual stresses in complex geometries parts. Due to the residual stresses relief, smooth specimens with greater warpage showed lower residual stresses. It was observed that the physical restraint used to restrain warpage assisted the retention of residual stresses in the polymer structure. Therefore, considering the resources used in this study, it was showed that the warpage is related to the product geometry, to the process parameters, the post-molding conditions and the residual stress relief existing in the injection molded polypropylene structure.
A qualidade final dos produtos poliméricos moldados por injeção pode ser comprometida devido à ocorrência de tensões residuais provenientes do processo de moldagem, as quais podem gerar contrações e empenamentos, alterando as dimensionais finais do produto. A determinação das tensões residuais pode ser realizada pelo método do furo cego, ensaio pouco difundido para materiais poliméricos pois é normalizado para materiais metálicos. Assim, com o objetivo de avaliar os parâmetros que influenciam nas alterações dimensionais e nas tensões residuais do polipropileno moldado por injeção, este trabalho utilizou simulações computacionais, análises térmicas, medições de empenamento e contração, ensaios de resistência à tração e ao impacto e avaliação das tensões residuais via método do furo cego. Após a moldagem, os corpos de prova foram submetidos a três condições pós-moldagem (restrição física + água, restrição física + estufa, neutro). Nos ensaios experimentais os corpos de prova moldados com menores pressões de recalque, como também os moldados com nervuras apresentaram maiores empenamentos, o que corroborou as simulações computacionais e a literatura. Nas condições pós-moldagem observou-se que os corpos de prova lisos submetidos à restrição física + estufa apresentaram menores empenamentos em relação aos que não foram submetidos à essa condição. Em relação às contrações, para ambas as geometrias dos corpos de prova, não houve variações significativas das médias. A análise térmica apontou menor grau de cristalinidade nas amostras com condição pós-moldagem neutra em relação à condição restrição física + estufa. As análises das tensões residuais concluíram que os corpos de prova com nervuras apresentaram tensões residuais superiores aos corpos de prova lisos, o que corroborou a literatura que indica maior concentração de tensões residuais em peças de geometrias complexas. Devido ao alívio das tensões, os corpos de prova lisos com maiores empenamentos apresentaram menores tensões residuais. Foi observado que a restrição física utilizada para restringir o empenamento auxiliou na retenção das tensões residuais na estrutura do polímero. Assim, considerando os recursos utilizados neste estudo, mostrou-se que o empenamento está relacionado com a geometria do produto, com os parâmetros de processo, com as condições pós-moldagem e com o alívio de tensões residuais existentes na estrutura do polipropileno moldado por injeção.
Keywords: Polipropileno; Tensões residuais; Moldagem por injeção de plástico; Resistência de materiais; Engenharia mecânica; Polypropylene; Residual stresses; Injection molding of plastics; Strength of materials; Mechanical engineering